2001
DOI: 10.2307/3069338
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Family Ties in Agency Contracts.

Abstract: Drawing on data based on the entire population of Spanish newspapers over 27 years , this study shows that firm performance and business risk are much stronger predictors of chief executive tenure when a firm's owners and its executive have family ties and that the organizational consequences of CEO dismissal are more favorable when the replaced CEO is a member of the family owning the firm. The study also demonstrates that executives operating under weakly relational (less ambiguous) contracts are held more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
485
2
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 959 publications
(525 citation statements)
references
References 53 publications
15
485
2
23
Order By: Relevance
“…Baek and Fazio (2015) also observed that family firms design agency contracts with less incentive mechanisms for family CEOs, especially when they receive material dividends. Interestingly, the authors offer a distinct rationale to explain their results, suggesting that family firms deviate from the tenets of agency contracting, as suggested by Schulze et al (2001) and Gomez-Mejia et al (2001).…”
Section: Related Literature Executive Pay and Incentive Compensation mentioning
confidence: 99%
“…Baek and Fazio (2015) also observed that family firms design agency contracts with less incentive mechanisms for family CEOs, especially when they receive material dividends. Interestingly, the authors offer a distinct rationale to explain their results, suggesting that family firms deviate from the tenets of agency contracting, as suggested by Schulze et al (2001) and Gomez-Mejia et al (2001).…”
Section: Related Literature Executive Pay and Incentive Compensation mentioning
confidence: 99%
“…On the one hand, there is an incentive for the owner to take actions that increase their personal utility, reducing corporate performance, which may be associated with less efficient investment decisions (Cronqvist & Nilsson, 2003). On the other hand, Gomez-Mejia et al (2001) suggest that as the concentration of family ownership increases there is an influence of family control over managers/directors, which can lead to greater entrenchment. The inversion of the concavity of the quadratic relationship, over that obtained in other studies focusing on large enterprises, may be related to the fact that the latter possess external control systems, professional management and more dispersed ownership where the holders of the equity purchase and sell shares in high liquidity securities markets.…”
Section: Ownership Concentration and Firm Operational Performancementioning
confidence: 99%
“…In intermediate levels of insider ownership convergence costs (coincidence of ideas about how to run the business) outweigh gains and interest between managers and other owners may differ (Del Brio, Maia-Ramires, & De Miguel, 2011). In order to maximize their own interest managers/directors can divert results and other company assets under their control, enjoy higher remuneration, place unqualified relatives in management positions, or become irreplaceable (La Porta, López, Shleifer, A., & Vishny, 2000, Gomez-Mejia, Nunez-Nickel, & Gutierrez, 2001). …”
Section: Insider Ownership and Performancementioning
confidence: 99%
“…The social connection that is built will be crucial for the firm owners to gain the major control in the corporation, especially in the annual general meeting (Gomez-Mejia et al, 2001). The binding will usually link up with the members that have the kinship connection.…”
Section: Binding Social Tiesmentioning
confidence: 99%